926 nm Yb-doped fiber femtosecond laser system for two-photon microscopy. (20th February 2019) - Wang, Pinghe; Xu, Xin; Guo, Zhengru; Jin, Xingjie; Shi, Guohua
Abstract: A Yb-doped fiber femtosecond laser system operating at 926 nm for two-photon microscopy is demonstrated. The laser system includes a master oscillator power-amplifier system, and the output wavelength shifts from 1064 nm to 926 nm by employing the nonlinear effect in photonics crystal fiber. The laser system produces 88 fs pulse train with 3.3 nJ pulse energy, 78 MHz repetition and 253 mW output power. The two-photon fluorescent image of a mouse kidney section proves that our femtosecond Yb-doped fiber laser system is an ideal source for two-photon microscopy.